The Effects of Surface Treatment and Plasticization on Properties of Kenaf Filled Poly (Lactic Acid) Composites - Othman, Maizatulnisa (2010)
The main objective of this study is to produce low cost environmental friendly materials (biocomposites)for food containers to replace the existing synthetic polymer materials such polyvinyl choride (PVC) , polypropylene (PP) and polyethylene terepthalate (PET), which are not green product and non-compostable materials. The main materials for this product are the poly(lactic acid) as a biodegradable polymer matrix and kenaf bast fibre (KBF) as a reinforcement. This research consists of four interconnected parts: the study of biocomposites materials on the effects of the fibre loadings, the modification on the fibre surfaces with sodium hydroxide (NaOH) in order to roughen the fibre surface, the modification of poly(lactic acid) with the plasticizers, and the enhancement on the polymer composite materials by combining the surface modification treated fibres with the plasticized poly(lactic acid) to have more green materials with good performances. Research and development on the poly(lactic acid) were conducted to modify the rigidity properties of the polymer itself, through the addition of triacetin and glycerol as plasticizers. These types of plasticizer are functionally compatible with the poly(lactic acid). This research was also done on fibre reinforcement to synergistically use the short KBF which has been effectively surface treated in order to improve the fibre matrix adhesion in the resulting bio-composites materials. The incorporation of KBF with PLA, with more than 30 wt% fibre loading, has been found to improve the tensile strength and modulus, whereas loading with higher percentage reduces the tensile and modulus value. Meanwhile, the thermal stability of the materials reveals that the PLA matrix and KBF have lower thermal stability as compared to the PLA/ KBF composites. The thermogravimetric analysis shows that 30 wt% of KBF loading has less amount of water content in fibres as compared to 50 wt% KBF loading, hence improves the strength of the composites. Water absorption analysis revealed that the water uptake increased with the increase of the KBF loading filled PLA matrix. The surface modification treatment with 4% of NaOH on KBF enhanced the plasticized PLA/KBF tensile strength, flexural strength, and impact strength as compared to plasticized PLA with untreated KBF composite systems. Dynamic mechanical analysis showed that with treated fibres, the composite had an increment in the storage modulus that was attributed to the enhancement of the fibre matrix adhesion. Tg from the loss modulus results showed that the plasticized PLA with the treated KBF composites shifted to a higher temperature. The addition of 5% triacetin and glycerol as plasticizers to modify the brittleness of PLA demonstrated that the plasticized PLA/KBF, with good mechanical and thermo-mechanical properties, have been developed. Triacetin improves the compatibility between the PLA matrix and KBF, whereas this is vice versa for the glycerol. The tensile strength properties of the plasticized PLA/KBF composites materials were significantly higher than those plasticized PLA/KBF with glycerol. The scanning electron microscopy photograph of the PLA/KBF composites plasticized with triacetin indicated the extent of the fibre-matrix interface adhesion. Meanwhile, the dynamic mechanical analysis showed that the PLA/KBF composites with triacetin have higher storage modulus as compared to the PLA/KBF with glycerol which corresponds to higher tensile modulus. The addition of both plasticizers has also been found to lower the softening temperature of the composites. The biodegradability test showed that the increase in the fibre content in the PLA produced a rapid decrease in the percentage of weight loss by bacteria and fungi during the soil burial process. The degradation time taken by the PLA/treated KBF with glycerol is longer than those of the plasticized PLA/treated KBF composites with triacetin. KBF filled with plasticized PLA bio-composites is environmental friendly and degradable, in addition to the fact that it can be considered as an alternative to conventional plastic materials such as polypropylene for packaging, food containers and disposable products.